Manajemen Strategis Ukraina dalam Perang Ukraina vs Rusia: Analisis Melalui Kerangka SWOT - Wahyu, Syamsul; Almubaroq, Hikmat Zakky; Suprapto, Suprapto (CV. AFDIFAL MAJU BERKAH, 2024)
The conflict between Ukraine and Russia has significant implications for Ukraine's strategic management, presenting challenges across military, economic, and political dimensions. This article provides a comprehensive analysis of Ukraine's strategic management approach using the SWOT (Strengths, Weaknesses, Opportunities, and Threats) framework. Ukraine's strengths include a strong national identity, support from Western allies, and a capable military, which have helped maintain its sovereignty despite Russian aggression. However, weaknesses such as economic challenges, internal political divisions, and dependence on Western support hinder its independence and strategic position. Opportunities for Ukraine lie in building stronger alliances with Western countries, overcoming economic challenges, and implementing diplomatic initiatives. These efforts can provide financial and military assistance, address economic issues, and achieve goals through negotiation. Threats to Ukraine include Russian military power, economic coercion, and political interference, which limit Ukraine's ability to achieve its objectives and make it vulnerable to regional pressures. This paper examines Ukraine's strategic position in the conflict, considering geopolitical dynamics, military capabilities, and historical context, highlighting the strategic management approach through the SWOT framework.